2022
DOI: 10.1021/acscatal.2c01880
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Recoverable vs Unrecoverable Voltage Losses and Long-Term Degradation Mechanisms in Anion Exchange Membrane Fuel Cells

Abstract: Anion exchange membrane fuel cells (AEMFCs) have recently shown excellent progress in terms of their performance – e.g., achievable power and current density. However, very few AEMFCs have been demonstrated with the ability to operate for a long duration (>1000 h). In addition, it is unknown whether performance losses observed during operation are reversible, irreversible, or a combination of the two. In this study, a high-performance AEMFC operated continuously at 600 mA/cm2 for 3600 h (150 days) at 80 °C wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…To this end, Mustain et al continued their previous study and investigated the cell durability mechanism and performance loss reversibility. 196,483 As claimed in the previous work, the authors employed benchmark electrocatalysts (PtRu/C for anode and Pt/C for cathode), ionomers, and GDEs, and achieved a stable operation of 2000 h. 196 Within this period of 2000 h, the cell average degradation rate nearly maintains at 15 mV h À1 (Fig. 32a).…”
Section: Membrane Electrode Assembly (Mea)mentioning
confidence: 59%
“…To this end, Mustain et al continued their previous study and investigated the cell durability mechanism and performance loss reversibility. 196,483 As claimed in the previous work, the authors employed benchmark electrocatalysts (PtRu/C for anode and Pt/C for cathode), ionomers, and GDEs, and achieved a stable operation of 2000 h. 196 Within this period of 2000 h, the cell average degradation rate nearly maintains at 15 mV h À1 (Fig. 32a).…”
Section: Membrane Electrode Assembly (Mea)mentioning
confidence: 59%
“…Also, it is evident from the RRDE results that the Fe 1 Co 2 -ZNT-900 catalyst showed about 17.6% lower HO 2 − yield when compared to the Fe 1 Co 1 -ZNT-900 catalyst, which affects the overall ORR kinetics and pathway that is reflected by the better AEMFC performance of the Fe 1 Co 2 -ZNT-900 catalyst. Most importantly, in the voltage range considered suitable for practical AEMFC use (between 0.8 and 0.6 V), 73,74 Fe 1 Co 2 -ZNT-900 outperforms the Pt/C cathode. This is ascribed to the effective mass transport of reactants at the active sites in the electrodes due to the hierarchical porous texture in the catalyst materials.…”
Section: Aemfc Performancementioning
confidence: 99%
“…These data present the dependency of the peak power density per square centimeter of geometric area on total PGM loading. It is no doubt that we expect to achieve relatively high performance at [99] 2012, [100] 2015, [101] 2017, [102] 2018, [90] 2019, [88,96] 2020, [67] 2021, [89] 2022 [106] (in H 2 -O 2 ) and 2010, [98] 2015, [103] 2017, [104] 2018, [90] 2019, [88] 2020, [97] 2021, [105] 2022 [74] (in H 2 -air). low PGM loading, as high specific peak power output means high catalyst utilization, which is very beneficial for cost reduction.…”
Section: Source Membranementioning
confidence: 99%
“…Improved cell component materials and reasonable operating parameters can not only improve the power density but also have a positive impact on durability. Figure 12 summarizes stability-related data retrieved from the literature, [72,88,89,96,97,105,106,[141][142][143][144][145] showing voltage changes with time at a constant current density. The performance of most AEMFCs is significantly reduced in the first 200 h of operation, and only a few studies in the literature have reported stability test data by considering over 200 h. In the study conducted by Zhao et al, [142] the authors found that the unloading pressure at 200 h and 400 h can increase the voltage by about 100 mV, indicating that releasing the pressure can improve water management and accelerate the electrochemical reaction to enhance cell stability.…”
Section: Aemfc Durabilitymentioning
confidence: 99%